Erwin Knecht—the intelligent and mad, funny and grumpy man of autophagy. Issue 4 (3rd April 2022) - Knecht, Erwin; Klionsky, Daniel J.
ABSTRACT: Getting to know Erwin Knecht is not so simple. This view was summarized in a comment from Dr. Marta Martinez Vicente, who obtained her PhD degree working in a lab that shared space with Erwin's group: "Erwin Knecht is a complex character, who awakens contradictory feelings. To define him I would say that he is a mixture of intelligence and madness, he's witty, very funny but also grumpy and cranky, all mixed and all simultaneously. Without a doubt he is a person who will not leave anyone indifferent, his original personality marked all who crossed his path, doctoral students, collaborators, people who attended his talks, etc … I remember the weekly lab meetings with him; we, the students, had a lot of respect for him (not to mention fear), but his comments were always smart, helpful and constructive, he has always been prone to helping everyone. In the lab, he was extremely demanding, but got people under his supervision to do their best. And despite his usual moodiness, he managed to make everyone love him and have a special affection for him. Above all, I remember his screams throughout the laboratory that could be heard from all over the building, calling out to his laboratory technician: 'Asunción!' They were like an old couple, arguing all day but they couldn't be without each other, it was like watching a sitcom every day." If you are intrigued, please read on.